(untitled) (Philological Studies, 2019)
The aim of our research was to review of Momčilo Nastasijević’s fiction (written and published largely during the 1920s), while primarily focusing on its development and its positioning in the context of the current moment and the history of Serbian literature. Therefore, we started dealing with our problem by considering the questions related to Nastasijević’s explicit poetics, essays, notes and thoughts, concluding, in the end, that his work defies strict contextualization. In a brief overview of the immediate reception (and inevitably with a retrospection of the further reception of Nastasijević’s work) we also traced the course of our writer’s inclusion among the greats of Serbian literature, culturologically a very interesting process.